PRINCIPALS’ PERCEPTION OF THE APPLICATION OF COST BENEFIT ANALYSIS IN ANAMBRA STATE SECONDARY SCHOOLS - Ikediugwu, Nkechi (Sokoto Educational Review, 2020)
The study investigated the application of Cost Benefit Analysis in Anambra State Secondary Schools. 258 Principals and 258 Bursars formed the population of the study. Three research questions and one hypothesis guided the study. A thirty item questionnaire was used to collect data. Data collected was analysed using mean scores and t-test statistics. It was discovered that the principals and bursars do not apply cost benefit analysis in spending the money approved for them. Secondly the State Education Commission that approved the N100.00 per child do not supervise how the money is being used. It was recommended among other things that State Education should start organizing Seminars and Workshops on financial management for principals. State Education Commission should also endeavour to monitor and supervise the N100.00 per child approved for principals.